The Role of KH. Bagus Amirullah in Handling the Maladaptive Behavior Students in class II (H) Men's Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan for the 2022-2023 Academic Year - Muhamad Ganjar Kurnia; Totok Agus Suryanto (Penerbit Hellow Pustaka, 2025)
The aim of this research is to find out how KH. Bagus Amirullah plays a role in dealing with maladaptive behavior in students in class II (H) Putra Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan for the 2022-2023 academic year. The research method used in this research is to use a descriptive method with a qualitative approach, because the aim of this research is to describe and provide an explanation regarding the role of KH. Bagus Amirullah in dealing with maladaptive behavior in students in class II (H) Putra Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan for the 2022-2023 academic year. The data collection technique in this study was to conduct interviews and retrieve documentation. The results of this research are KH. Bagus Amirullah divides maladaptive behavior into 3 criteria, namely mild maladaptive behavior, moderate maladaptive behavior and severe maladaptive behavior. The role that KH. Bagus Amirullah plays in dealing with the maladaptive behavior of class II (H) students, Son of Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan for the 2022-2023 academic year is as a motivator for students who have lazy maladaptive behavior and as a spiritual teacher for students who have maladaptive behavior with severe criteria. Based on the results of interviews with students who had received guidance from KH. Bagus Amirullah, they stated that they were starting to be able to abandon bad habits and get used to good habits.